DINAMIKA HUBUNGAN KELUARGA DAN LANSIA DALAM KEPUTUSAN MEMILIH PANTI JOMPO : STUDI KASUS PANTI SOSIAL LANJUT USIA HARAPAN KITA LUBUKLINGGAU - Irvina, Zaleha (Program Studi Bimbingan dan Konseling Pendidikan Islam, 2025)
This study aims to analyse the dynamics of family relationships and elderly people in the decision-making process of choosing a nursing home as a place of residence. This decision is influenced by various factors, such as the personal preferences of the elderly, family considerations, physical and mental health conditions, and social situations such as living alone without family support. The study uses a qualitative approach with data collection techniques through interviews, observation, and documentation. The results show that the decision of the elderly to enter a nursing home can be voluntary based on the need for comfort, companionship, and care. However, some decisions involve the family considering time constraints, the ability to provide care at home, and the emotional dynamics between family members. Some elderly people also enter nursing homes due to physical limitations or mental disorders that hinder their independence. In addition, social factors such as the absence of family are a dominant reason. These findings emphasise the importance of family communication, social support, and responsive community service systems so that the decisions made can meet the overall welfare of the elderly and their families.